Gene action and combing ability of some agronomic traits in corn using diallel analysis - Haddadi, Mohammad Hossein; Esmaeilov, Maqsadollah; Choukan, Rajab; Rameeh, Valiollah (Plant Breeding and Seed Science, 2014)
Combining ability estimates are important genetic attributes to maize breeders in anticipating improvement via hybridization and selection. To determine the combining ability for yield and yield associated traits, 8 diverse corn inbred lines were used in a half diallel mating design. Twenty eight F1 progenies along with their parents were planted in randomized complete block design with four replications in two locations during two years. Combined analysis of variance showed significant mean squares of general combining ability (GCA) and specific combing ability (SCA) for Days to silking emergence (DS), plant height (PH), 1000-kernel weight (KW), number of kernels in ear row (KR), number of rows in ear( NR ) , ear diameter (ED), cob diameter (CD), kernel yield (KY) indicating that the importance of both additive and non additive genetic effects for these traits. However, high narrow-sense heritability estimates, low degree of dominance and the ratio of estimates of GCA to SCA effects for DS , NR and CD indicated that additive genetic effect was more important for these traits. Most of the crosses with significant SCA effects for KY had at least one parent with significant GCA effects for the same traits. Significant positive correlations were detected between KY and other yield components including KW, KR, NR and ED, therefore these traits can be used as indirect selection criteria for KY improvement. The crosses MO17 × Line8, MO17 × Line 10 and MO17 × Line 12, Line 8 × Line 10 and Line 8 × Line 21 with high values of KY were considered as good cross combinations for improving the trait.